PERANCANGAN PENDETEKSI KEBOCORAN GAS LPG DENGAN SENSOR MQ-5 BERBASIS ARDUINO - ARI SUCI NOVIAN (POLITEKNIK PIKSI GANESHA, 2018)
Now a days, almost all households have LPG gas stove for their daily use after the central goverment embarking a massive convertion program from kerosene to LPG (Liquid Petroleum Gas) a few years ago. LPG Stove has many advantages, It is More efficient and more practice compared with conventional stove that use kerosene as its fuel. But there is one problem that still worried its users related hazards that can be inflicted in case of leakage of the gas. Fires, Explosion and gas poisoning are some examples of the massive dangers that can arise because of the gas leakage. Based on that condition, It is needed gas leakage detector and with its danger sign. To develop this automatic tool for Mitra Keluarga and this tool is created to prevent the occurrence of fires caused by gas leakage. Microcontroller that used to control all this tool components is Arduino Uno R3 and gas sensor use MQ-5. This tool equipped with LCD screen to show information about gas concent and installed with an Information system that can automatically send sms if gas leakage is detected.